Coronavirus disease and basic sanitation: too early to be worried? - Renata Rocha da Silva; Márcio Bezerra dos Santos; Allan Dantas dos Santos; Débora dos Santos Tavares; Priscila Lima dos Santos (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: Considering that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been detected in feces, this study aimed to verify a possible relationship between basic sanitation indices and coronavirus disease (COVID-19) numbers/rates. METHODS: Data of COVID-19 cases registered in Brazil until May 28, 2020, and independent variables associated with basic sanitation were analyzed. RESULTS: A significant correlation between the number of cases and sewage treatment index/population density was observed. In addition, COVID-19 incidence and mortality rates were significantly associated with the total water service index and lethality rate was significantly associated with the sewage treatment index. CONCLUSIONS: Precarious basic sanitation infrastructure may potentially increase the SARS-CoV-2 transmission in Brazil.